Comparative study of caudal clonidine and midazolam added to bupivacaine during infra-umbilical surgeries in children - Sadhana Sanwatsarkar; Sahil Kapur; Dipti Saxena; Gaurav Yadav; Nagina Naz Khan (Wolters Kluwer Medknow Publications, 2017)
Background and Aims: Caudal analgesia is a good, reliable, and easy method to provide intraoperative and postoperative analgesia for infra-umbilical surgeries in children. Many additives are being used in combination with local anesthetics in caudal block to prolong the postoperative analgesia (clonidine, midazolam, ketamine, fentanyl, and dexmedetomidine). The purpose of this study was to compare the intraoperative hemodynamics, postoperative analgesia, postoperative rescue analgesic requirement, postoperative sedation and side-effects of clonidine and midazolam used as adjuvants to bupivacaine for caudal analgesia. Material and Methods: Following approval from Institutional Ethical Research Committee, 75 American Society of Anesthesiologists I and II patients aged between 1 and 7 years undergoing various elective infra-umbilical surgical procedures were included in this study. The patients were randomly allocated into three groups of 25 patients each. Group B received 1 ml/kg 0.25% bupivacaine in normal saline, Group BC received 1 ml/kg 0.25% bupivacaine + 1 μg/kg clonidine in normal saline, and Group BM received 1ml/kg 0.25% bupivacaine + 30 μg/kg midazolam in normal saline. The various parameters studied were intraoperative hemodynamic changes, duration of postoperative analgesia, postoperative sedation, postoperative analgesic requirement, and incidence of side-effects. Results: All the groups were similar with respect to patient and block characteristics. The hemodynamic parameters before and after administering caudal analgesia were also comparable. The mean duration of analgesia was 724.80 ± 60.29 min in Group BC, 605.40 ± 82.37 min in Group BM and 295.00 ± 41.78 min in Group B. Thus, the duration of analgesia was significantly prolonged in Group BC compared to Groups BM and B. The FLACC pain score was higher in Group B at the end of 4th, 8th and 12th h compared with Group BC and Group BM. Furthermore at the end of 12th h, pain scores were significantly higher in Group BM compared to Group BC. Only 1 child in Group BC received three rescue medications compared to 15 (60%) children in Group B and 7 (28%) children in Group BM. None of the groups were treated for bradycardia or hypotension and no significant sedation was noted. Conclusion: This study showed that the addition of both clonidine (1 μg/kg) and midazolam (30 μg/kg) with bupivacaine administered caudally significantly increase the duration of postoperative analgesia with minimal side-effects in children. The use of clonidine as an additive to bupivacaine in caudal epidural is a superior choice to midazolam as it reduces the demand of postoperative rescue analgesics significantly.